Life Cycle Assessment (LCA) pada Permohonan Kartu Keluarga Baru (Penambahan Anggota Keluarga Bayi/Anak). Studi Kasus: J-SIP DISPENDUKCAPIL JEMBER - Dimyati, Aufar Fikri (Journal of Comprehensive Science, 2025)
This study compares the life cycle inventory (LCI) of family card application services conducted online (via the J-SIP application) and offline (conventional) at DISPENDUKCAPIL Jember. The analysis focuses on identifying the environmental impact, particularly the carbon footprint, generated by both service methods. Data collection includes energy consumption, material usage (paper), and transportation emissions at each stage of the process. The results indicate that the online service significantly reduces environmental impact compared to the offline service. The carbon footprint of the online service is 865.6 grams of CO2 lower, representing a 92.3% reduction compared to the offline service. This reduction is primarily due to decreased transportation emissions, as the implementation of digital infrastructure (J-SIP) eliminates the need for the public to travel by motorcycle to submit and complete their applications. These findings highlight the potential benefits of digital transformation in public services in achieving sustainability goals from a carbon footprint perspective.